Etos Kerja Mapalus dalam Penguatan Moderasi Beragama Masyarakat Kampung Jawa Tondano - Nainggolan, Alon Mandimpu; Kandowangko, Lidya; Situmorang, Yehezkiel; Heydemans, Nency Aprilia; Lahamendu, Natalia (Tatar Pasundan: Jurnal Diklat Keagamaan, 2024)
The purpose of this study is to describe Mapalus Work Ethic (mutual collaboration of Minahasa culture) in Christian-Islamic interactions in Kampung JaTon Minahasa. The approach employed is phenomenology, which involves observation and in-depth interviews. The study's findings reveal that Mapalus' local knowledge serves as a reinforcer, unifier, and adhesive for religious groups in Tondano Java, which is consistent with religious moderation indicators. Mapalus ideals and religious moderation practices in Kampung Java-Tondano include openness, togetherness, and tolerance. This study concludes that establishing religious moderation based on local wisdom is vital and relevant to execute since it positively helps building peace between religious communities.Keywords: Work ethic; Mapalus; Religious Moderation; Tondano Java.